Adsorption of particulate matter and uptake of metal and non-metal elements from PM in leaves of Pinus densiflora and Quercus acutissima: a comparative study - Lee, Jongkyu; Kwak, Myeong Ja; Woo, Su Young (Frontiers in Forests and Global Change, 2024)
Trees can serve as effective biofilters of Particulate matter (PM) pollution, making them valuable for managing air pollution and promoting public health. Leaves of trees can reduce PM through absorption, adsorption, and fallout mechanisms, which are influenced by species-specific characteristics and environmental factors. Although several studies have explored the impact of various leaf characteristics on their ability to adsorb PM from field conditions, few have been conducted in controlled chambers to analyze the adsorption of PM on leaf surfaces and the uptake of metal and non-metal elements from PM on leaves. To fill these knowledge gaps, this study investigated the PM adsorption and leaf characteristics of two different tree species, Pinus densiflora (an evergreen coniferous species) and Quercus acutissima (a deciduous broad-leaved species) under controlled conditions in a PM exposure chamber with a target concentration of 300 μg m−3. The main aim of this study was to measure and compare the rate of PM component (metal and non-metal elements) uptake in two species and investigate the leaf characteristics that contribute to PM adsorption. We investigated the relationship between PM adsorption and physiolog, micro-morphology, and chemical properties of the leaf surface in two species. This study used a Pearson’s correlation analysis and a principal component analysis (PCA) to evaluate correlation between PM adsorption and leaf characteristics and uptake of metal/non-metal elements in PM on leaves. This result showed that leaf characteristics such as stomatal size, leaf roughness, and wax content played a crucial role in PM10 adsorption, while physiological factors like transpiration and leaf boundary layer conductance were identified as important determinants of PM2.5 adsorption on plant leaves. It also observed significant variations in the uptake of aluminum, iron, magnesium, phosphorus, and sulfur. This study not only advances our understanding of the mechanisms behind PM adsorption by tree leaves but also underscores the importance of selecting appropriate tree species based on their leaf characteristics for urban forestry and green infrastructure projects. The ability to strategically use tree species for PM pollution mitigation highlights a practical approach to enhancing environmental sustainability and public health.